Effect of flow on corrosion of water pipelines in petrochemical industry. Issue 1 (February 2021) - Lin, Nan; Li, Cong; Luo, Yanlong; Jiang, Ping; He, Renyang; Zhang, Jibo
Abstract: Effect of flow on corrosion of inner wall of metal pipelines is complex, relationship between them has not been fully revealed yet in existing researches. In petrochemical industry, leakage of water pipelines often occurs. Once sewage pipelines leaking, serious pollution may happen. Therefore, valid researches on effect of flow on corrosion could provide a theoretical basis for process designing and inspection planning of water pipelines in petrochemical industry. In this paper, the static and flow induced corrosion were discussed according to the experimental results, the acceleration and influence of the velocity on flow induced corrosion were discussed.